Peran Industri Perkebunan Dalam Meningatkan Kesejahteraan Masyarakat Sekitar Prespektif Maqashid Syariah : (Studi Kasus PT. Jhonlin Batu Mandiri) - Mahfudz, Mahfudz; Rahman, Muljibir; Wahid Mongkito, Abdul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
Community welfare is a mandate of law and religious orders, so that citizens must get welfare, namely that their needs must be fulfilled, can carry out their religious teachings and receive proper education and teaching. in Indonesia alone the level of community welfare is still low, still at 21.9% in 2019. To overcome welfare problems, the presence of the plantation industry PT. Jhonlin Batu Mandiri is a good choice to solve the problem of community welfare, so in this study the authors analyze the extent to which the role of PT. Jhonlin Batu Mandiri in solving community welfare problems, both in the concept of state law and the concept of maqashid sharia. This study uses a qualitative approach with interviews, observations and documentation.